Assistance in Writing Narrative Text Skills Based on Local Wisdom to Improve Critical Thinking in MA AL-Ittihad Tawangsari Mojokerto Students - Jayanti, Rani; Sholikah, Amilatus; Hanum, Nur Kholida; Lestari, Tiwi Widya; Mayangsari, Salsa Devista; Hamidah, Adila Nisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to improve the ability to write narrative texts and critical thinking of MA Al-Ittihad Tawangsari Mojokerto students through local wisdom-based writing skills mentoring. The process involved three main stages: narrative writing assistance, improvement of critical thinking skills, and evaluation measurement. The implementation was conducted on April 27, 2024 with the participation of 7 students through a quantitative approach with data results in the form of numbers and statistics. The results showed that the skill of writing narrative texts with local wisdom had a significant increase in the ability to write narratives and students' critical thinking. The implication is the importance of incorporating local wisdom in learning to increase the relevance and meaning of learning for students, and the need for support and training for educators in implementing this approach effectively.